2017
DOI: 10.1103/physrevc.95.034308
|View full text |Cite
|
Sign up to set email alerts
|

Exact solution of the mean-field plus separable pairing model reexamined

Abstract: Exact solution of the nuclear mean-field plus separable pairing model is reexamined. New auxiliary constraints for solving the Bethe ansatz equations of the model are proposed. By using these auxiliary constraints, the Bethe ansatz form of eigenvectors of the mean-field plus separable pairing Hamiltonian with non-degenerate single-particle energies and non-degenerate separable pairing strengths purposed previously is verified. Since the solutions of the model with one-and two-orbit cases are known, verificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The separable pairing problem was studied in [25], in which the single-particle energies are all degenerate. The separable pairing interaction with two non-degenerate levels was analyzed in [26], of which solution with multi non-degenerate levels of a special case was given in [27][28][29], while the general case has been analyzed in [30]. In this work, it will be shown that the orbit-dependent non-separable pairing interaction among valence nucleons over two non-degenerate orbits can also be solved analytically.…”
mentioning
confidence: 99%
“…The separable pairing problem was studied in [25], in which the single-particle energies are all degenerate. The separable pairing interaction with two non-degenerate levels was analyzed in [26], of which solution with multi non-degenerate levels of a special case was given in [27][28][29], while the general case has been analyzed in [30]. In this work, it will be shown that the orbit-dependent non-separable pairing interaction among valence nucleons over two non-degenerate orbits can also be solved analytically.…”
mentioning
confidence: 99%
“…Richardson [49] explained the method to exactly solve the pure pairing model including non-degenerate single-particle orbits for both fermion and boson systems. Extensions to the Richardson-Gaudin theory have been made using the Bethe ansatz methodology, [50][51][52][53].…”
Section: Pairing Hamiltonian and Quasi-spin Limitmentioning
confidence: 99%